1983
DOI: 10.1128/iai.41.3.1175-1183.1983
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of the rabbit small intestine by clinical and environmental isolates of non-O1 Vibrio cholerae and Vibrio mimicus

Abstract: We examined the capability of 12 isolates of non-cholera toxin-producing 01 and non-O1 Vibrio cholerae to colonize the small intestine of adult rabbits and cause diarrhea. Using the removable intestinal tie-adult rabbit diarrhea model, we found that eight environmental isolates that showed no or marginal biological activity in other diarrhea models (rabbit ileal loop, infant rabbit, and suckling mouse) appeared to be incapable of attaching to and colonizing, even transiently,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Therefore, in contrast to 987P and K99 fimbriae, TCP and BFP expression is expected to be activated at an earlier stage of infection. Consistent with this, colonization by V. cholerae (Nelson et al, 1976;Cray et al, 1983;Spira et al, 1983;Pierce et al, 1985) and EPEC (Ulshen and Rollo, 1980;Rothbaum et al, 1982; has been described to involve proximal as well as distal segments of the small intestine.…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, in contrast to 987P and K99 fimbriae, TCP and BFP expression is expected to be activated at an earlier stage of infection. Consistent with this, colonization by V. cholerae (Nelson et al, 1976;Cray et al, 1983;Spira et al, 1983;Pierce et al, 1985) and EPEC (Ulshen and Rollo, 1980;Rothbaum et al, 1982; has been described to involve proximal as well as distal segments of the small intestine.…”
Section: Discussionmentioning
confidence: 52%
“…It is also noteworthy that this bacterium is capable of producing haemolysins, a group of toxins considered to constitute a common pathogenic factor shared by various species of the genus Vibrio [19]. In addition, Spira et al [20] reported that the majority of isolates from diarrhoeal stools displayed this characteristic, and the Table 2 Results assay with non-01 V cholerae in animal model (permeability factor and fluid accumulation) same characteristic was observed in 89.7% of isolates taken from the environment [1]. In this study, haemolysin was detected in 63.28% of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Colonization of rabbit small intestinal mucosa by clinical and environmental isolates of V. cholerae and V. mimicus was shown (25). Correlation has been established between in vitro adherence to intestinal epithelium of human (26) and rabbit (14) and the cell-associated haemagglutination of V. cholerae.…”
Section: Activation Of Cell-associated Vm-omphamentioning
confidence: 94%
“…Correlation between the adherence and the cellmediated haemagglutination has been established for many intestinal pathogens (10,18,25,26), and cell surface proteins, such as haemagglutinins (HAs) and/or different types of pili, presumably accomplish both bacterial phenomena (20). In Vibrio cholerae, the etiologic agent of cholera, the toxin-coregulated pilus (TCP) has been documented to be essential for adherence of the classical biotype strains (13); however, the mannosesensitive HA as well as TCP has been implicated in the case of the El Tor strains (21).…”
mentioning
confidence: 99%